The updated data on the leaf beetle diversity (Coleoptera, Chrysomelidae) of Algeti National Park and its environs (Georgia, Caucasus) - Nino Gabroshvili; Oxana Nesterova; Nana Bakhtadze (Travaux du Muséum National d’Histoire Naturelle “Grigore Antipa”, 2025)
The species diversity of the leaf beetles was investigated in Algeti National Park and its environs (Georgia, Caucasus). Forty-eight species of leaf beetles belonging to 23 genera are listed. Among the taxa two genera and six species are recorded for the first time in the investigated area: Agelastica Chevrolat, Leptinotarsa Chevrolat, Agelastica alni Linnaeus, Coptocephala rubicunda rossica Laicharting, Cryptocephalus duplicatus Suffrian, Labidostomis longimana Linnaeus, Leptinotarsa decemlineata Say and Smaragdina xanthaspis Germar. A checklist of the chrysomelids of Algeti National Park and its environs is presented for the first time.